Biologia e predação de Atopozelus opsimus Elkins, 1954 (Hemiptera: Reduviidae) sobre pragas do eucalipto - Souza, Caroline Dias de [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
O predador Atopozelus opsimus Elkins, 1954 (Hemiptera: Reduviidae) é um percevejo nativo considerado um potencial agente de controle biológico de pragas. O inseto já foi relatado se alimentando de Diaphorina citri Kuwayama, 1908 (Hemiptera: Liviidae), Glycaspis brimblecombei Moore, 1964 (Hemiptera: Aphalaridae), Leptocybe invasa Fisher e LaSalle, 2004 (Hymenoptera: Eulophidae), Mastigimas anjosi Burckhardt (Hemiptera: Calophyidae), Musca domestica Linnaeus, 1758 (Diptera: Muscidae) e Thaumastocoris peregrinus Carpinteiro e Dellapé, 2006 (Hemiptera: Thaumastocoridae). Os insetos G. brimblecombei, L. invasa, T. peregrinus e Thyrinteina arnobia Stoll, 1782 (Lepidoptera: Geometridae) constituem o grupo das principais pragas do eucalipto no Brasil, podendo ser manejados com produtos químicos, genótipos resistentes e agentes de controle biológico, sendo essa última a principal ferramenta utilizada. Para compreender o controle biológico e a eficiência dos inimigos naturais, estudos sobre os aspectos biológicos e comportamentais são de extrema importância, porém, são poucas as pesquisas envolvendo A. opsimus. O objetivo foi estudar a predação, sobrevivência e comportamento de A. opsimus sobre pragas do eucalipto. Durante o desenvolvimento as ninfas de primeiro ínstar do predador consumiram menos T. peregrinus a 30 °C que a 18, 21 e 24 °C. O número predado no segundo ínstar foi maior a 21 °C, que a 27 e 30 °C. No terceiro ínstar a predação foi maior a 18 °C que a 21 e 30 °C. O consumo pelo quarto e quinto ínstar do predador foi semelhante a 24, 27 e 30 °C e 27 e 30 °C, respectivamente. As curvas de sobrevivência de A. opsimus com T. peregrinus a 30 °C foram menores para todos os ínstares, com 100% de mortalidade de ninfas de primeiro, segundo, terceiro, quarto e quinto ínstares em 13, 17, 22, 26 e 30 dias, respectivamente. As curvas de sobrevivência foram maiores nas menores temperaturas avaliadas. A proporção média predada de adultos de G. brimblecombei e T. peregrinus por adultos de A. opsimus foi maior nas temperaturas mais elevadas testadas. O ganho médio de massa de A. opsimus ao se alimentar de G. brimblecombei e T. peregrinus aumentou conforme a elevação da temperatura. Os tempos gastos por A. opsimus no forrageamento das quatro pragas testadas não diferiram, variando de 2,94 minutos com T. arnobia a 7,77 minutos com T. peregrinus. A autolimpeza ocorreu por mais tempo quando em contato com T. arnobia, 53,92 minutos, e menos com L. invasa e G. brimblecombei, 18,11 e 20,04 minutos, respectivamente. Os tempos utilizados na predação foram semelhantes, variando de 70,83 a 179,90 minutos com T. peregrinus e L. invasa, respectivamente. Os tempos gastos em outros comportamentos não diferiram, variando de 158,33 a 272,49 minutos em L. invasa e T. peregrinus, respectivamente. Para o predador, T. peregrinus e T. arnobia são similarmente atrativos comparados ao G. brimblecombei e L. invasa. O psilídeo-de-concha é mais atrativo à A. opsimus que a vespa-da-galha. O psilídeo-de-concha G. brimblecombei e a vespa-da-galha L. invasa são as presas preferidas pelo predador.

The predator Atopozelus opsimus Elkins, 1954 (Hemiptera: Reduviidae) is a native bug, considered a potential agent of biological pest control. The insect has been reported feeding on Diaphorina citri Kuwayama, 1908 (Hemiptera: Liviidae), Glycaspis brimblecombei Moore, 1964 (Hemiptera: Aphalaridae), Leptocybe invasa Fisher and LaSalle, 2004 (Hymenoptera: Eulophidae), Mastigimas anjosi Burckhardt (Hemiptera: Calophyidae), Musca domestica Linnaeus, 1758 (Diptera: Muscidae) and Thaumastocoris peregrinus Carpinteiro and Dellapé, 2006 (Hemiptera: Thaumastocoridae). The insects G. brimblecombei, L. invasa, T. peregrinus and Thyrinteina arnobia Stoll, 1782 (Lepidoptera: Geometridae) constitute the group of the main pests of eucalyptus in Brazil, and can be managed with chemical products, resistant genotypes and biological control agents, the last is the main tool used. To understand the biological control and the efficiency of natural enemies, studies on biological and behavioral aspects are extremely important, however, there is few research involving A. opsimus. The objective was to study the predation, survival and behavior of A. opsimus on eucalyptus pests. During the development, the predator's first instar nymphs consumed less T. peregrinus at 30 ° C than at 18, 21 and 24 ° C. The number predated in the second instar was higher at 21 ° C, than at 27 and 30 ° C. In the third instar, predation was higher at 18 ° C than at 21 and 30 ° C. The consumption by the predator's fourth and fifth instars was similar to 24, 27 and 30 ° C and 27 and 30 ° C, respectively. The survival curves of A. opsimus with T. peregrinus at 30 ° C were lower for all instars, with 100% mortality for nymphs of first, second, third, fourth and fifth instars in 13, 17, 22, 26 and 30 days, respectively. The survival curves were higher at the lowest temperatures evaluated. The predated average proportion of adults of G. brimblecombei and T. peregrinus by adults of A. opsimus was higher at the highest temperatures tested. The average mass gain of A. opsimus when fed on G. brimblecombei and T. peregrinus increased with increasing temperature. The time spent by A. opsimus in the foraging of the four tested pests did not differ, varying from 2.94 minutes with T. arnobia to 7.77 minutes with T. peregrinus. Self-cleaning occurred for a longer time when in contact with T. arnobia, 53.92 minutes, and less with L. invasa and G. brimblecombei, 18.11 and 20.04 minutes, respectively. The time used in the predation were similar, varying from 70.83 to 179.90 minutes with T. peregrinus and L. invasa, respectively. The time spent on other behaviors did not differ, ranging from 158.33 to 272.49 minutes in L. invasa and T. peregrinus, respectively. For the predator, T. peregrinus and T. arnobia are similarly attractive compared to G. brimblecombei and L. invasa. The red gum lerp psyllid is more attractive to A. opsimus than the gall wasp. The red gum lerp psyllid G. brimblecombei and the gall wasp L. invasa are the prey preferred by the predator.
Biology and predation of Atopozelus opsimus Elkins, 1954 (Hemiptera: Reduviidae) on eucalyptus pests
Keywords: Controle biológico; Percevejo predador; Eucalyptus; Pragas; Biological control; Predator; Forest pests